A clinical study of diphtheria cases in a pediatric population in tertiary care hospital in western Maharashtra - Bandichhode, Sachin T; Jatti, Gajanan M; Anita, M S; Nandimath, Viresh A (Indian Journal of Child Health, 2016)
Background: Although DPT immunization has been a part of universal immunization program since its inception, still diphtheria continues to be endemic in India and also leading to morbidity in children, especially in areas in the border of the two states. Cases coming to tertiary care level are only tip of iceberg. Objectives: To study the clinical profile, morbidity, and mortality of the diphtheria cases admitted to the Pediatrics Department of a tertiary care hospital and to study their immunization status. Materials and Methods: A hospital-based cross-sectional study was conducted from 1 January, 2012, to 31 June, 2013, on clinically suspected diphtheria cases. Detailed history and clinical examination were done, and their immunization status was recorded. Results: Total 36 clinically suspected children of diphtheria were studied. Sex ratio was 1:1. 12 cases were from 1 to 5 years age group, whereas 15 cases were between 6 and 10 years and remaining 9 cases aged more than 10 years. Among 36 cases, 4 (11.11%) were fully, 11 (30.55%) were partially immunized, and 21 (58.33%) were not immunized. The most common symptom observed was fever in 34 (94.44%) cases followed by throat pain in 25 (69.44%) cases and difficulty in swallowing in 23 (63.88%) cases. Case fatality rate was 13.88%. Maximum numbers of cases were observed during the rainy season. Conclusion: High prevalence of diphtheria in the age group of 5-15 years suggests the need for completing immunization schedule specially booster doses. Immunization activity needs to be strengthened in borderline districts as most of the cases in the present study were from the areas in the border between states.